Constraints of Virtually Using Digital-Based Learning Media for Early Childhood Education Teachers - Tetty Muharmi (International Journal Reglement & Society (IJRS), 2022)
Our world of education in Indonesia in general and in North Sumatra in particular is facing several problems and dilemmas. From the aspect of teaching materials, it is clear that it has not been fully resolved because there are still many students who still face obstacles related to the lack of teaching materials, especially for early childhood teachers in various regions in North Sumatra in particular. The type of research used in this research is normative juridical. The nature of this research is descriptive analytical. The learning model needs to be set according to the existing situation and conditions. Early childhood teachers use learning to overcome problems of effectiveness and efficiency of learning in the midst of limited learning facilities and online learning policies during the Covid-19 Pandemic. Online learning for early childhood teachers is carried out for theoretical learning, while for practical activities, practice is required by using simulations or virtual practical applications.